Duped: why innocent people confess and why we believe their confessions - Kassin, Saul (Prometheus, 2022)
The Problem in a Nutshell -- "Off-the-Books" False Confessions -- "Liar, Liar, Pants on Fire!" - Police as Human Lie Detectors -- Psychological Interrogation: Getting Inside your Head -- Hollywood Confessions: Lights, Action, Camera -- Forensic Confirmation Bias: How Confessions Corrupt Witnesses and CSI Experts -- Why False Confessors Plead Guilty - Over and Over Again -- Confessions at Trial: Why Little Else Matters to the Judge and Jury -- Confession Blindness: Why the Stigma Persists -- Your Right to Remain Silent - Safeguard or Trap? -- Proposed Reforms to Policy and Practice.